2018
DOI: 10.1016/j.envexpbot.2017.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of C4 decarboxylation and photosynthetic plasticity in sugarcane plants under shading

Abstract:  Sugarcane grown under low light showed increased PEPCK activity.  Changes in chloroplast arrangements in bundle sheath cells were also observed.  Such morpho-physiological adjustments maintained C4 photosynthetic efficiency.  A model considering carboxylation and decarboxylation pathways is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 49 publications
5
31
0
Order By: Relevance
“…3a, b). It has been speculated that this enzyme provides the necessary ATP to increase PEPCK activity for sugarcane plants under stress [11, 32]. Western Blot analyses showed that plant species that use predominantly PEPCK have significant levels of NAD-ME [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3a, b). It has been speculated that this enzyme provides the necessary ATP to increase PEPCK activity for sugarcane plants under stress [11, 32]. Western Blot analyses showed that plant species that use predominantly PEPCK have significant levels of NAD-ME [33].…”
Section: Discussionmentioning
confidence: 99%
“…The rise in PEPCK activity can be modulated by various environmental factors [5, 11]. Specifically in sugarcane, shading caused increases in the decarboxylation by PEPCK, which shows that this enzyme is the main decarboxylase under low light conditions [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shade acclimation in C 4 species has been studied primarily by comparing plants grown in high vs. low light (Tazoe et al, 2008;Sales et al, 2018;Sonawane et al, 2018). On this basis, it has been observed that C 4 species have relatively poor acclimation to shade relative to C 3 species (Sage and McKown, 2006), but C 4 grasses which use the NADP-ME subtype, such as Z. mays, acclimate to shade more readily than those using NAD-ME or PEP-CK subtypes (Sonawane et al, 2018).…”
Section: Introductionmentioning
confidence: 99%